Single Maritime Boundary and Dual Maritime Regimes: Case Study of Indonesia - Djundjunan, Bebeb Abdul Kurnia Nugraha; Adolf, Huala; Siswandi, Achmad Gusman; Agusman, Damos Dumali (UI Scholars Hub, 2024)
Various judgements of international tribunals have shown a trend of the use of Single Maritime Boundary (SMB) in solving maritime boundary disputes. The application of SMB by international tribunals are based on the submission of the parties in dispute, typically to simplify the maritime boundary delimitation process. The concept of the SMB line, which puts the Exclusive Economic Zone and Continental Shelf boundaries into one line, has grown into a deceptive perspective when taking into account that the provisions under the 1982 UNCLOS, particularly Articles 74 and 83, are the same. The application of SMBs is likely to be disadvantageous for Archipelagic States. Studies based on several cases such as the Gulf of Maine, Libya/Malta, Qatar/Bahrain, and Bangladesh/Myanmar indicate that certain perspectives of “judicial” SMBs is accepted by State practices. Nevertheless, in the Qatar/Bahrain case, the preference to establish separate or single line relies on the States themselves. Despite the growing trend to implement SMBs, Indonesia has consistently acknowledged the distinct regimes of the Exclusive Economic Zone and Continental Shelf, as stipulated in the 1982 UNCLOS. Since the entry into force of the 1982 UNCLOS, Indonesia’s position on delimitation emphasizes on the distinction between the Exclusive Economic Zone and the Continental Shelf. Under Indonesia’s practices, the agreed negotiation may be done by extracting two lines in the same agreement or one line in two different agreements. This article will examine the Single Maritime Boundary under international law as well as related state practices and Indonesia perspective and experiences.